2003
DOI: 10.2337/diacare.26.11.2983
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thiazolidinediones and Risk of Heart Failure in People With Type 2 Diabetes

Abstract: OBJECTIVE -To compare the incidence of heart failure in individuals with type 2 diabetes receiving thiazolidinediones (TZDs) versus other oral antihyperglycemic agents.RESEARCH DESIGN AND METHODS -We conducted a retrospective cohort study using a health insurance claims database. The study sample included patients with type 2 diabetes who received an oral antihyperglycemic agent between January 1995 and March 2001. Those with any claims for TZDs were designated "exposed," and each was compared with five random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(114 citation statements)
references
References 22 publications
5
106
0
1
Order By: Relevance
“…A higher risk of heart failure has been reported in some studies (25), whereas others have actually suggested a reduced risk of heart failure in glitazone-treated patients (26). A recent analysis demonstrated reduced mortality in patients with a prior history of heart failure who were treated with glitazones (27).…”
Section: Glitazones: Other Considerationsmentioning
confidence: 99%
“…A higher risk of heart failure has been reported in some studies (25), whereas others have actually suggested a reduced risk of heart failure in glitazone-treated patients (26). A recent analysis demonstrated reduced mortality in patients with a prior history of heart failure who were treated with glitazones (27).…”
Section: Glitazones: Other Considerationsmentioning
confidence: 99%
“…It has been shown that claims data can identify cardiovascular endpoints with very high specificity, resulting in relatively small potential for bias associated with misclassification of the outcome [124][125][126][127][128]. Among the evaluated literature, few explorative analyses assessed the potential effect of outcome misclassification on the study estimates [68,70].…”
Section: Other Issuesmentioning
confidence: 99%
“…Subjects will be balanced with regard to all baseline covariates and follow-up will start after the accumulation of pre-specified levels of dispensed dose or treatment duration. Few studies included analyses assessing the effect of cumulative exposure to glucose-lowering agents [11,12,19,37,45,47,49,61,68].…”
Section: Temporality Considerations In Administrative Databasesmentioning
confidence: 99%
“…The latter, which can be explained by PPARg stimulation of ENaC-mediated renal salt absorption [218], might be the cause of an increased incidence of congestive heart failure [219], an outcome also observed in rats where rosiglitazone treatment is associated with increased post-myocardial infarction mortality [220]. However, this issue is still under debate as the Prospective Pioglitazone Clinical Trial in Macrovascular Events (PROactive) showed recently that treatment of type 2 diabetic patients with pioglitazone, another TZD drug, improved their cardiovascular outcome [113].…”
Section: Use Of Synthetic Pparg Agonists In the Treatment Of Lipodystmentioning
confidence: 99%